Appraising the Coverage of Gender in Geography Education in Uganda Secondary Schools - Kagoda, Alice Merab (Advances in Social Sciences Research Journal, 2017)
Geography is an interdisciplinary subject which includes both the physical and human components. It is about the relationship between the people and the physical environment, as well as the interaction among people themselves. The environment in which people live changes in time and space making geography a dynamic subject which call for constant change in the content and the methodology of teaching it. Gender is one of the current issues in society which help to explain the low levels of development in most developing countries. This paper critically examined the O-level geography to identify topics where it can be integrated, as well as, recommending methods can be used to teach it. The author recommends that the government of Uganda should integrate gender in the geography teaching syllabus, train teacher through in-service programmes to sensitize them about the importance and values or integrating gender in the subject. The Uganda National Examinations Board should be oriented to current issues in education and set questions relevant and appropriate to gender issues.